Análise de viabilidade econômico-financeira em uma empresa produtora de camarão na cidade de Aracati-CE: um comparativo de métricas - Monteiro, Fillypi Jarbem Damasceno (Universidade Federal Rural do Semi-Árido, 2020)
The research aimed to financially evaluate the capital investment project in the shrimp production on a typical property in the lower Jaguaribe region in the state of Ceará, using the methodologies classic and multi-index of financial viability analysis. In a complementary way, the total variation of the financial indicators was measured, through risk analysis, seeking to modify the amount of shrimp produced annually. The results pointed to a realistic scenario where the investment made is considered viable with indicators, such as: NPV at R$ 710.297,24; 27.01% IRR, Simple Payback of three years and ten months; Discounted Payback of four years and two months; NAV of R$ 89,766.53; IBC of R $ 3.39 and ROIA at 12.97%. These results indicate that shrimp farming represents, for the rural sector of the state of Ceará, an important investment alternative, because, even considering price risk, the IRR value was 27.01%, what means, any other investment would only be desirable, in comparison with the investment in the shrimp production, if it presented a rate of return above this value.
Keywords: Análise de viabilidade financeira; indicadores financeiros; análise de risco; carcinicultura; ENGENHARIAS::ENGENHARIA DE PRODUCAO